CONSEQUENCES OF STATE PRICE REGULATION - MOROZ, SERGIY; MEISH, ALLA; VOVKOTRUB, CATHERINE (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In the modern minds of the functioning of the national economy, it is an important tool for the state regulation of social and economic processes and the price and price of policy. The policy of value is the main importance of the economic and social policy of any state. It’s a matter of time, when you’re in charge of ideas, besides that, it’s blame for the power’s involvement in the economy, and it’s injected into the processes of price maintenance, such as methods and tools for the price regulation of overwhelming pressure.The article considers the essence of state regulation of prices on the example of individual markets: electricity, medicines and agricultural products. The economic consequences of state regulation of prices in the modern conditions of functioning of the national economy of Ukraine are analyzed. It is studied that the degree and forms of state intervention in pricing processes depends on the state of socio-economic development of the country, the specific gravity of public sector, the degree of private property, the level of monopolization and competition, the intensity of information processes and many other factors. It was found that state fixed and regulated prices and tariffs are set by public authorities.
Keywords: price; pricing; state pricing policy; state price regulation; shortage; balanced price; self-regulation of market; shadow market; commodity intervention; export restrictions; consumption subsidies; tariff restrictions